Patient-centered quality measurement for opioid use disorder: Development of a taxonomy to address gaps in research and practice. Issue 1 (1st December 2022) - Kelley, A. Taylor; Incze, Michael A.; Baylis, Jacob D.; Calder, Spencer G.; Weiner, Saul J.; Zickmund, Susan L.; Jones, Audrey L.; Vanneman, Megan E.; Conroy, Molly B.; Gordon, Adam J.; Bridges, John F.P.
Abstract: Background : Evidence-based treatment is provided infrequently and inconsistently to patients with opioid use disorder (OUD). Treatment guidelines call for high-quality, patient-centered care that meets individual preferences and needs, but it is unclear whether current quality measures address individualized aspects of care and whether measures of patient-centered OUD care are supported by evidence. Methods : We conducted an environmental scan of OUD care quality to (1) evaluate patient-centeredness in current OUD quality measures endorsed by national agencies and in national OUD treatment guidelines; and (2) review literature evidence for patient-centered care in OUD diagnosis and management, including gaps in current guidelines, performance data, and quality measures. We then synthesized these findings to develop a new quality measurement taxonomy that incorporates patient-centered aspects of care and identifies priority areas for future research and quality measure development. Results : Across 31 endorsed OUD quality measures, only two measures of patient experience incorporated patient preferences and needs, while national guidelines emphasized providing patient-centered care. Among 689 articles reviewed, evidence varied for practices of patient-centered care. Many practices were supported by guidelines and substantial evidence, while others lacked evidence despite guideline support. Our synthesis of findings resulted in EQuIITable Care, a taxonomy comprised of six classifications: (1) patient E xperience and engagement, (2) Qu ality of life; (3) I dentification of patient risks; (4) I nterventions to mitigate patient risks; (5) T reatment; and (6) Care coordination and navigation. Conclusions : Current quality measurement for OUD lacks patient-centeredness. EQuIITable Care for OUD provides a roadmap to develop measures of patient-centered care for OUD.